The dietary regime of detritivorous fish from the River Jacaré Pepira, Brazil - Vaz, M. M.; Petrere, M. [UNESP]; Martinelli, L. A.; Mozeto, A. A. (Wiley, 1999)
The diet of detritivorous fish was analysed at four distinct habitats in a tropical river during the wet and dry seasons. Two methodologies were used to determine the diet of the fish: (1) the direct analysis of the stomach contents; and (2) the use of stable carbon isotopes. Both methods indicated food partitioning among the fish. The stomach contents showed what the fish had ingested when captured and the 13C isotope indicated what it had assimilated over a long period of time. The 13C isotope suggested the existence of sectional differences in the feeding of the detritivorous fish along the river. Plants employing the C4 photosynthesis pathways seem to have little influence on the diet of these fish. This method proved to be more appropriate for the detection of the main food sources of the captured fish.
Keywords: Autotrophic energy sources; Detritivorous fish; Feeding ecology; Stable carbon isotopes; Stomach contents; carbon 13; detritivory; diet; fish; stomach content; Brazil; Characiformes; Siluriformes